Public Sentiment Toward the “Curriculum of Love” Policy in Islamic Education: Evidence from YouTube Discourse in Indonesia - Hamdan Hamdan; Ansor Ansor; Awal Kurnia Putra Nasution; Suhono Suhono (Attractive : Innovative Education Journal, 2026)
Recent education reforms have increasingly turned toward the moral and affective dimensions of learning in response to concerns about social fragmentation and ethical decline. In Islamic educational traditions, moral formation has never been peripheral; it has long been treated as a central pedagogical aim. Yet contemporary reforms framed in moral language often provoke mixed reactions once they enter public debate. This study examines how the Indonesian public responds to the “Curriculum of Love” policy in Islamic education by analysing YouTube discourse as a site of digital engagement. The study draws on an exploratory sentiment analysis of 145 opinion-based comments taken from seven YouTube videos produced by government agencies, practitioner communities, and national media. Comments were manually coded as positive, neutral, or negative and interpreted through thematic analysis to trace the narratives accompanying each sentiment. Overall sentiment trends toward support, particularly in videos that showcase classroom practice and lived pedagogical examples. Many viewers interpret the policy as consistent with Islamic ethical values and character formation. At the same time, a sizeable portion of responses express skepticism, focusing on the gap between symbolic rhetoric and institutional capacity, as well as anxieties about ideological boundaries. Sentiment patterns vary markedly across communication formats, indicating that public reception depends not only on the policy itself but on how it is communicated. Rather than signaling simple acceptance or rejection, online reactions reveal an ongoing negotiation over the meaning and credibility of reform. The findings suggest that digital discourse functions as a space where Islamic education policy is publicly tested, contested, and interpreted. By combining sentiment analysis with qualitative interpretation, this study offers a framework for understanding how value-based education reforms gain — or struggle to gain — legitimacy in contemporary digital environments.